Detection of SARS-CoV-2 in the tears and conjunctival secretions of Coronavirus disease 2019 patients - Kaya, Hüseyin; Çalışkan, Ahmet; Okul, Mehmet; Sarı, Tuğba; Akbudak, İsmail Hakkı (The Journal of Infection in Developing Countries, 2020)
Introduction: Current studies suggest that tears and conjunctival secretions may be an important transmission route in coronavirus disease 2019 (COVID-19). The study aims to evaluate the presence of severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) virus in tears and conjunctival secretion of patients with COVID-19. Methodology: A prospective interventional case series study was performed, and 32 patients with COVID-19 were selected at the Pamukkale University Hospital from 15 to 22 May 2020. The tear and conjunctival samples were collected by a conjunctival swab. Each specimen was sent to the laboratory for reverse transcription-polymerase chain reaction (RT-PCR) analyses. To avoid cross-infection, gloves and personal protective equipment were changed after collecting each sample. Results: 32 patients (18 male, 14 female) with Covid-19 were included in this cross-sectional study. The average age of the patients was 52.81 ± 16.76 years. By the time of the first collection of conjunctival-tear samples, the mean time of the onset of complaints was 6.84 ± 6.81 (1-35) days. Tear-conjunctival samples from 5 patients (16%) without conjunctivitis yielded positive PCR results, 3 of whom had positive and 2 negative nasopharyngeal PCR results. Conclusions: Five of 32 patients (16 %) without conjunctivitis or any eye symptoms had viral RNA in their tear-conjunctival samples. The possibility of transmission via tears and conjunctival secretions should be recognized even in the absence of conjunctivitis or other ocular manifestations.